The concept and main features of the primary sources of law of the European Union - Amanbayeva, Zhanna (European Integration Studies, 2023)
The European Union’s (EU) sources of law, which fall under the generic definition of a source of law, each have unique characteristics. This article examines the dual nature of the EU law and addresses the issues with its concepts and features. The sources of EU law are classified as primary and secondary. The primary sources include constituent agreements and general principles of law, while the secondary sources comprise regulations, directives, and framework decisions.